Internationalization of SMEs : the challange of selecting foreign market entry modes - Gustavsson, Sara; Lundgren, Erica (2006)
This thesis focuses on how SMEs select foreign market entry modes. To be able to gain a better understanding of the subject, research questions concerning SMEs’ motives for internationalization, approaches to foreign market entry mode and influence of internal factors were formulated. The empirical data consisted of case studies of two Swedish companies active within the wood industry and located in northern Sweden. Findings show the main motive for SMEs to go international is the level of demand for SMEs’ products in foreign markets. In order for the SMEs to be able to compete on the foreign market they have to have unique products with flexible price setting. SMEs, due to their small size and limited resources, are more or less forced to use more simple and less costly entry modes, thus, most companies begin their internationalization with various forms of the export mode where less control and fewer resources to move abroad is needed. Validerat; 20101217 (root)